(untitled) (JTT (Jurnal Teknologi Terpadu), 2021)
Indonesia is a large archipelago country with various characteristic areas. Based on a report from the Ministry of Energy and Mineral Resources, Indonesia’s electrification ratio has reached 98.86%. Even though Indonesia’s electrification ratio is close to 100%, it cannot be denied that there are still many remote areas that still do not have electricity supply. This can be caused by areas that are difficult to reach, thus hampering the construction of the electricity network. To meet electricity needs in remote areas and with not too many population, a Diesel Power Plant (PLTD) is usually built, but this type of plant requires fuel oil which of course also requires replenishment every certain time after the fuel runs out. To solve the above problems, a portable solar power plant (PLTS) is proposed which can be easily mobilized to facilitate delivery to remote areas. PLTS portable can also be used as an emergency power source in areas where electricity facilities have been cut off due to natural disasters. To adjust the output voltage of the solar panels, a single input multi output (SIMO) converter topology is proposed. This converter consists of a flyback converter that can increase and decrease the voltage and has isolation between the input and output sides. In addition, this converter also has several outputs so that it can supply two loads (battery and communication equipment) at the same time. To maximize the conversion of solar energy in this system, it is also proposed to use the MPPT control with the PSO method.